PERANCANGAN IDENTITY KEMASAN MAKANAN TRADISIONAL “DADIAH” DI GADUIK BUKITTINGGI - RAENDRAIOGI HERLLY, Ir. Drs. Heldi, M.Si. Ph.D., Hendra Afriwan, S.Sn., M.Sn. (DEKAVE : Jurnal Desain Komunikasi Visual, 2017)
The purpose of identity Dadiah packaging design is to create identity Dadiah a new packaging without losing its traditional form (native). So that, it can be known by the public and to tourists who visit West Sumatra, commonly in Gaduik particular area, Bukittinggi with Dadiah new packaging design with modern form combined with traditional form.The design method begins with data collection, observation, interviews and documentation. So that, the problem occur in the packaging Dadiah promotion can be discovered from identify of that problem by conducting a SWOT analysis.The design is result major media like packaging that is packaged in a cardboard that displays visualization and information nutritional value of traditional food Dadiah. The main media is completed by supporting media which are poster, x-banners, T-shirts, flayers, business cards, key chains, stickers, tote bag and bamboo plastic covers.Keywords: design, Identity, promotion, packaging, Dadiah.